2012
DOI: 10.3892/etm.2012.563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PSCA gene polymorphisms on gastric cancer risk and survival prediction: A meta-analysis

Abstract: Abstract. Previous studies have shown that two single-nucleotide polymorphisms (SNPs) in PSCA (rs2976392 and rs2294008) are associated with gastric cancer (GC), but the results are conflicting. Additionally, the prognostic value of PSCA gene polymorphisms for GC patients is unknown. We performed a meta-analysis using 9 eligible case-control studies to investigate the association between PSCA polymorphisms and GC risk, and additionally investigated the prognostic value of PSCA polymorphisms for GC patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
4
8
0
Order By: Relevance
“…Consistently with studies in Europeans and meta-analyses of studies in Asians [5], [11], [29], [30], we observe an association of this SNP with all histological types of GC, without any statistically significant evidence for difference in risk between GC subtypes according to histology or location. It should be noticed however that the sample size of the subgroups in this study is rather small.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistently with studies in Europeans and meta-analyses of studies in Asians [5], [11], [29], [30], we observe an association of this SNP with all histological types of GC, without any statistically significant evidence for difference in risk between GC subtypes according to histology or location. It should be noticed however that the sample size of the subgroups in this study is rather small.…”
Section: Discussionsupporting
confidence: 90%
“…Several case-control studies confirmed the association of this SNP with GC in Asian and Caucasian populations. Meta-analyses [10], [11], [29], [30] showed ORs ranging between 1.41–1.66 for the dominant model and between 1.14–1.33 for the recessive model. The two other PSCA SNPs of our study were previously found to be associated with GC risk in Europeans [6].…”
Section: Discussionmentioning
confidence: 99%
“…Qiao et al [44] included eight studies from seven publications with a total of 9738 gastric cancer cases and 7054 controls, and concluded that rs2294008 T allele and rs2976392 A allele were significantly associated with increased gastric cancer risk. These findings were confirmed by other meta-analysis [45-48]. The most recent meta-analysis by Gu et al [49] involved 16 studies.…”
Section: Discussionsupporting
confidence: 67%
“…Qiao et al [ 42 ] included eight case-control studies from seven articles and found that rs2294008 T allele and rs2976392 A allele were significantly associated with increased gastric cancer risk. These findings were also confirmed by other meta-analysis [ 43 46 ]. More recently, to access the contributions of these two widely investigated PSCA SNPs to gastric cancer susceptibility, Gu et al [ 47 ] performed a meta-analysis of 16 studies with a total of 18,820 cases and 35,756 controls.…”
Section: Discussionsupporting
confidence: 86%